Membership and morals : the personal uses of pluralism in America - Rosenblum, Nancy L. (Nancy Lipton), 1947- (Princeton University Press, 1998)
In recent years, membership has dropped in traditional voluntary associations such as Rotary Clubs, Jaycees, and bowling leagues. At the same time, concern is rising about the growth of paramilitary and hate groups. In this provocative book, however, Nancy Rosenblum takes a new, less narrowly political approach to the study of groups. And she reaches more optimistic conclusions about the state of civil society. Rosenblum argues that we should judge associations not only by what they do for civic virtue, but also by what they do for individual members. She shows that groups of all kinds - among them religious groups, corporations, homeowners associations, secret societies, racial and cultural identity groups, prayer groups, and even paramilitary groups - fill deep psychological and moral needs. And she contends that the failure to recognize this has contributed to an alarmist view of their social impact. Rosenblum concludes that, for practical and principled reasons, American democracy should permit expansive freedom of association, illustrating her case with discussion of specific cases in law. Rosenblum recognizes, however, that freedom has a price. She reminds us that some groups have oppressive and even criminal tendencies, and she explores what liberal democracy should do to ensure that individuals also have freedom within associations and freedom to exit.